Strategi Pengembangan Penerapan Web Checking Dalam Meningkatkan Operasional Penerbangan di PT. Citilink Indonesia - Rizal Bakti; Prista Helma Riyadi; Wahjuny Djamaa; Rio Eldianson; Rizkison Rizkison (Indonesian Journal of Multidisciplinary on Social and Technology, 2026)
This research aims to analyze internal and external environmental factors, determine the company's strategic position, and formulate alternative business development strategies that are suitable. The analysis methods used include SWOT analysis, IFE-EFE matrix, IE matrix, and QSPM (Quantitative Strategic Planning Matrix) to evaluate the strategic competitiveness of the company. The results show that internal factors such as a strong brand image and corporate parent support are the main strengths, while the low adoption of web check-ins is a weakness. External factors indicate opportunities through the improvement of digital services and threats from competitors as well as cybersecurity risks. The IFE score of 2.72 and EFE of 2.62 places Citilink in quadrant V of the IE matrix, namely the hold and maintain strategy. The main recommended strategy is to improve features and socialization of web check-ins with the highest QSPM score (3.24), accompanied by a strategy to strengthen the digital security system. The implementation of this strategy is expected to improve service efficiency, strengthen a competitive position, and support long-term business growth in the aviation digital market.